Penerapan Teknologi Tepat Guna Mesin Pencacah Sayuran Hijau untuk Meningkatkan Efisiensi Usaha Ternak Bebek - Suparmono; Suadi, Suadi; Khairina, Isni; Dewi, Ratna; Manurung, John Sihar (Politeknik Negeri Medan, 2025)
Feed costs are the largest component of duck farming and often pose a major constraint on the sustainability of small-scale farmers. This community service program aimed to apply appropriate technology, in the form of a green vegetable-chopping machine, to improve the efficiency of duck farming businesses. The partner was a household-scale laying duck farmer with approximately 300 ducks who partially substituted commercial feed with discarded green vegetables from traditional markets. The main problems were low feed intake efficiency due to whole-vegetable feeding and the absence of chopping equipment. The implementation methods included field surveys and situation analysis, machine design and fabrication, operational testing, training in operations and maintenance, and impact evaluation. The results showed that the vegetable chopping machine with A capacity of approximately 100 kg/hour and a 1 HP electric motor significantly improved the utilization of green feed. The application reduced commercial feed costs by about 25% and increased daily egg production by around 4–5%. This activity demonstrates that simple, affordable, and context-appropriate technology can effectively enhance business efficiency and economic resilience of small-scale duck farmers.